Information Technology and Service Delivery of County Governments in Western Kenya Region - Kennedy Wandera Walubengo; Fredrick Njehu Kiongera; Joshua Olango Abuya (International Journal of Business, Economics, and Social Development, 2023)
The inappropriateness in use of public monies has been cited as a major distractor towards achievement of development goals enshrined in our constitution. It has been largely attributed to the procurement practices adopted. The main objective of this study was to determine effects of information technology on service delivery of County governments in western Kenya region. The target population for this study entailed 228 officers who were categorized into chief officers, Directors, Finance officers and procurement officers. This study employed stratified random sampling towards picking a sample of 174 respondents. Information technology from the findings of this study had a significant effect on the delivery of services among counties in western Kenya region. Particularly, as Information technology changes by one unit, service delivery changes by 0.309 units units (β2=0.309, P<0.05). The F value obtained df (1,161) =84.947, P<0.05, that gave support to the goodness of fit of the model in adducing variance in the dependent variable. It meant too that Information Technology is a useful predictor of service delivery. This study therefore recommended that County Governments should view and treat information technology as a critical component and resource since its application in procurement activities improves delivery of services.